2018
DOI: 10.1073/pnas.1717135115
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic context of DRD1 is associated with prefrontal activity and behavior during working memory

Abstract: Dopamine D receptor (DR) signaling shapes prefrontal cortex (PFC) activity during working memory (WM). Previous reports found higher WM performance associated with alleles linked to greater expression of the gene coding for DRs (). However, there is no evidence on the relationship between genetic modulation of expression in PFC and patterns of prefrontal activity during WM. Furthermore, previous studies have not considered that DRs are part of a coregulated molecular environment, which may contribute to DR-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
(89 reference statements)
1
28
0
Order By: Relevance
“…To test the hypothesis if there is a relation between the altered functional connectivity in language-related areas and language-related gene mutations, we carried out a genetic association analysis using the pathway-based polygenic risk scores 18 , 19 , as gene sets centering on putative core function, or belonging to specific biologically relevant pathways, may make a larger-than-expected contribution to polygenic risk 21 , 66 . In particular, we chose the candidate genes that are related to schizophrenia, development, and language by combing knowledge from multiple sources, including existing literature, gene ontology analysis, and brain gene expression data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the hypothesis if there is a relation between the altered functional connectivity in language-related areas and language-related gene mutations, we carried out a genetic association analysis using the pathway-based polygenic risk scores 18 , 19 , as gene sets centering on putative core function, or belonging to specific biologically relevant pathways, may make a larger-than-expected contribution to polygenic risk 21 , 66 . In particular, we chose the candidate genes that are related to schizophrenia, development, and language by combing knowledge from multiple sources, including existing literature, gene ontology analysis, and brain gene expression data.…”
Section: Methodsmentioning
confidence: 99%
“…To this end we obtained pathway-specific polygenic risk scores (PRS) from language-related genes. Selecting a subset of genes that are grouped into the same pathway, or co-expressed with given candidate genes for calculating PRS, termed 'pathway-specific PRS' or biologically informed PRS [18][19][20] , is widely used in image genetics of psychiatric disorders including schizophrenia 21,22 . The goal of this work is to bridge the mechanistic gap between genetic variations and neuroimaging-based measure of brainwide dysconnectivity in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Following from the dual-state theory of network function, the stability of task-related brain states should be related to prefrontal D1 receptor status. To estimate individual prefrontal D1 receptor expression, we utilized methods relating prefrontal cortex D1 and D2 receptor expression to genetic variation in their co-expression partner (Online Methods), thereby enabling us to predict individual dopamine receptor expression levels from genotype data across the whole genome (12,13). We found that D1 (but not the D2) expression-related gene score predicted stability of both states ( Fig.…”
Section: Number Of References: 20/20mentioning
confidence: 99%
“…We used SPM12 to perform multiple regression analyses for both tasks and for the two samples separately. For the co-expression analysis, we used the linear and quadratic terms of PCImiR-137 (30,66,78) as predictors and age, gender, and five genomic eigenvariates as covariates. For the PRSmiR-137 analyses, we used PRSs as predictors and the same covariates reported above.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test systems-level phenotypes associated with the module of interest, we generated a Polygenic Co-expression Index (PCImiR-137). We identified SNPs in the module genes associated with the first principal component of module gene expression (a measure of co-expression of the whole module) and combined them into the PCImiR-137 (13,30,66) (SI-1.4). We estimated the effect of allelic dosage via a Robust Linear Model (rlm function -robust R package) and ranked SNPs according to their p-value (31).…”
Section: Biological Genetic Stratification Of Mir-137 Target Genes: Tmentioning
confidence: 99%